2010
DOI: 10.1111/j.1740-0929.2010.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between milk characteristics and somatic cell score in milk from primiparous browsing goats

Abstract: To determine milk yield and composition, total microbic count (TMC) and somatic cell count (SCC) of browsing goats throughout the first lactation, 100 goats of Sarda breed, equally distributed in four flocks (F1, F2, F3 and F4), were selected. They were exclusively fed pasture and hand-milked once daily. Individual milk samples and daily milk yield were taken from each goat at monthly intervals, from March to July. Milk samples were analyzed for: total protein, fat, lactose, urea, freezing point (FP), pH, TMC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
2
11
2
1
Order By: Relevance
“…Todaro et al (2005) reported a mean value of 426 000 cells/mL for Girgentana goat. Similar mean values of SCC (log 10 ) were reported by Vacca et al (2010) in local Sarda goat breed that, as Girgentana, is reared in a pastoral system, hand-milked and in the absence of modern husbandry techniques. High SCC in milk was associated with subclinical mastitis (Leitner et al 2004) and it leads to modification of main milk components with negative effects on cheese manufacture.…”
Section: Milk Yield and Gross Compositionsupporting
confidence: 63%
“…Todaro et al (2005) reported a mean value of 426 000 cells/mL for Girgentana goat. Similar mean values of SCC (log 10 ) were reported by Vacca et al (2010) in local Sarda goat breed that, as Girgentana, is reared in a pastoral system, hand-milked and in the absence of modern husbandry techniques. High SCC in milk was associated with subclinical mastitis (Leitner et al 2004) and it leads to modification of main milk components with negative effects on cheese manufacture.…”
Section: Milk Yield and Gross Compositionsupporting
confidence: 63%
“…Hadjipanayiotou () and Vacca et al . () also reported a direct relationship between these parameters, although the correlation coefficients were very low. In agreement with Vacca et al .…”
Section: Resultsmentioning
confidence: 93%
“…Vacca et al . () reported that the urea content in goat milk shows a bell‐shaped pattern, with the highest values being observed at intermediate points of the lactation period. According to this, it would seem that an increase in the urea concentration would occur during the first few hours after parturition, differing from what was observed in our study.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that the presence of CSN1S1 A in the Sarda goat may be due to the genetic influence of the Maltese breed, which for many years has been used to increase Sarda goat milk production (Vacca et al . ). The occurrence of the null CSN1S1 01 and N alleles, although in low percentage, enriches the genetic potential of the Sarda goat.…”
Section: Discussionmentioning
confidence: 97%